Changes of faecal microbiota in patients with Crohn's disease treated with an elemental diet and total parenteral nutrition - Shiga, Hisashi; Kajiura, Takayuki; Shinozaki, Junko; Takagi, Sho; Kinouchi, Yoshitaka; Takahashi, Seiichi; Negoro, Kenichi; Endo, Katsuya; Kakuta, Yoichi; Suzuki, Manabu; Shimosegawa, Tooru (Digestive and liver disease, 2012)
Intestinal microbiota contributes to the pathogenesis of Crohn's disease. Elemental diet and total parenteral nutrition are effective therapies for Crohn's disease; however, changes of microbiota as a result of both treatments have not been fully elucidated. To elucidate changes of faecal microbiota in Crohn's disease patients treated with elemental diet and total parenteral nutrition. Stool samples were collected from 33 active Crohn's disease patients and 17 healthy subjects, and recollected after elemental diet (8 patients) and total parenteral nutrition (9 patients). Terminal restriction fragment length polymorphism analysis of bacterial 16srDNA was performed to evaluate the whole microbiota. Specific quantitative PCR was then used to determine populations of predominant bacterial groups. In Crohn's disease patients, the number of terminal restriction fragments, which reflects bacterial species, was significantly lower. Populations of total bacteria and Bifidobacterium were significantly lower and the ratio of Enterococcus was higher. The number of terminal restriction fragments was significantly decreased after total parenteral nutrition, but not after elemental diet. Population of Bacteroides fragilis significantly decreased after elemental diet, while population of Enterococcus significantly increased after total parenteral nutrition. Faecal microbiota in Crohn's disease patients was markedly different from healthy subjects. Species diversity was reduced by total parenteral nutrition, but not by elemental diet.